Application of an ultrasound-guided bilateral erector spinae plane block after the Nuss procedure for pectus excavatum in children: a retrospective cohort study with propensity score matching - Wu, Shihuan; Wu, Jing; Zhang, Xifeng (Frontiers in Pediatrics, 2023)
Abstract Objective: To retrospectively analyze the effect of applying ultrasound-guided bilateral erector spine plane block (ESPB) after the Nuss procedure for surgical repair of pectus excavatum (PE) in children. Methods: The subjects of the study were patients with severe PE who received the Nuss procedure in our hospital from January 1, 2019 to November 30, 2021. According to different methods for postoperative pain management, the enrolled patients were divided into two groups, the ultrasound-guided ESPB group and the thoracic epidural analgesia (TEA) group. The results of analgesic drug dosage, numerical rating scales (NRS) and hospital stay were compared between the two groups. Results: There was no significant difference between the two groups in demographic, preoperative clinical evaluation or surgical characteristics (P>0.05). The catheter duration in TEA group was significantly shorter than that in ESPB group (P<0.05), while the hospitalization time in ESPB group was significantly shorter than that in TEA group (P<0.05). In terms of OME comparison, the required dose of TEA group was lower than that of ESPB group on the 1st and 2nd day after operation (P <0.05), and there was no statistical difference between the two groups on the 3rd and 4th day after operation (P >0.05). The number of patients with S-NRS ≥ 7 and D-NRS ≥ 7 in TEA group at day1 was lower than that in ESPB group (P <0.05). There was no significant difference between the two groups at other time points (P >0.05), Conclusion: Ultrasound-guided ESPB used in Nuss surgery for children with funnel chest can provide good analgesia for surgery and shorten the postoperative rehabilitation and hospitalization time of patients. It is a safe and effective alternative to TEA.